TECHNOLOGICAL DEVELOPMENT OF FSUE "RosRAO" AS A PART OF THE INDUSTRY-SPECIFIC INFRASTRUCTURE FOR PROCESSING, CONDITIONING AND STORAGE OF RADIOACTIVE WASTE - V. N. Kovalenko; O. A. Gorbunova (Тонкие химические технологии, 2016)
This article describes promising technological solutions for the processing, storage and transportation of radioactive waste (RW) implemented by a leading Russian enterprise specializing in the field of radioactive waste management. Federal State Unitary Enterprise "RosRAO" performs nationallevel tasks to ensure nuclear, radiation and environmental safety in the treatment of all types of radioactive waste. To date, FSUE "RosRAO" has a number of ready-made solutions aimed at saving resources while maintaining the radiation and environmental safety by reducing logistics costs due to using large containers for transportation and storage; maximum recycling of waste at the site of its formation or interim storage with the help of mobile systems; creation and operation of easily erected facilities for temporary storage of solid radioactive waste before transferring it for conditioning or disposal. In recent years, we completed a number of major projects focused on improving the radioecological situation on the territory of Russia. The Regional Centre for conditioning and long-term storage of radioactive waste, largest in Russia, was put into operation in Sayda Guba in Murmansk region. Works for state needs were performed to bring radiationhazardous objects to a safe state and to reclaim territories of the Russian Federation subjects exposed to radiation as a result of past activities in the Trans-Baikal and Stavropol territories, Kirov, Moscow, Ivanovo and Orenburg regions.